Enhancing soil quality in soybean cultivation: Mycorrhizal technology combined with intercropping under high cadmium stress - Xiaohui Wang; Xiaoxu Fan; Wei Chang; Kun Li; Mengmeng Zhang; Gaozhong Pu; Alexander.V. Kurakov; Yuan Ping; Fuqiang Song (Ecotoxicology and Environmental Safety)
Cadmium (Cd) contamination presents a serious challenges for sustainable agriculture. This study evaluated the combined impact of arbuscular mycorrhizal fungi (AMF) inoculation and intercropping with Solanum nigrum on soil microbial diversity, enzyme activity, and environmental factors in soybean cultivation under high Cd stress. The combined treatment effectively reduced bioavailable Cd in soil, with the acid-soluble Cd fraction at 19.57 mg/kg and the reducible Cd fraction at 61.35 %, resulting in safe soybean grain Cd levels (2.63 mg/kg, below the 3 mg/kg organic standard). Illumina NovaSeq sequencing analysis revealed that key bacterial taxa, including Bradyrhizobium and PMMR1, were correlated with reduced Cd uptake in grains. Although bacterial α diversity increased, microbial network stability decreased in response to Cd, AMF inoculation, and intercropping. The combined treatment also enhanced soil enzyme activity by regulating the relative abundance of dominant or key genera such as Subgroup_6, Rokubacteriales and Pseudarthrobacter. Notably, catalase activity was 97.25 % higher in the combined treatment compared to monoculture without AMF colonization under high Cd conditions. These findings demonstrate the synergistic potential of AMF inoculation and S. nigrum intercropping as a sustainable approach to mitigate Cd contamination in crops while improving soil health in Cd-contaminated environments.